Fraktur supracondylar os femur pada anjing English Bulldog - Albiruni Haryo; Ulvi Hudriyah; Muhamad Arfan Lesmana; Natasha K. Puspitasari (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
An English Bulldog named Dexter were admitted at Brawijaya University Veterinary Teaching Hospital with the anamnesis of undergoing a trauma of being hit by a car. The dog presented with avoiding using left hind leg, limping and pain when palpated. Radiographic imaging showed a closed complete fracture on distal femur, at the supracondylar region. The treatment for this case is using condylar plate and intramedullary pen (rod). There were no complication and the dog were sent go home after 6 day's post-surgery.